THE ROLE OF THE PRESS BOARD OF HOAX REPORTS TAKEN BY ANNOUNCER BASED ON PRESS LAW - Dwianto, Rizky Andi; Soediro, Soediro; Hidayah, Astika Nurul (UMPurwokerto Law Review, 2020)
In the era of digitalization and globalization like today, news or information can be obtained not only through print media but also through cyber media. However, what is unfortunate is the emergence of new media such as cyber media, not all are able to provide accurate, reliable and responsible information, instead, some of the cyber media, practice hoax reporting. The press council has the function to establish and oversee the implementation of the journalistic code of ethics, which is to give consideration and to seek resolution of public complaints on cases related to press reporting, including hoax reporting. In recent years, hoax news has emerged. This study discusses how the press council's role in hoax reporting is carried out by journalists based on Law Number 40 of 1999 concerning the Press and what are the obstacles experienced by the press council against hoax reporting carried out by journalists based on Law Number 40 Year 1999 About the Press. The method used in this study is the normative juridical method carried out through literature studies that examine mainly secondary data. The role of the press council on hoax reporting carried out by journalists based on Law Number 40 of 1999 Concerning the Press is oversight of the implementation of the Journalistic Code of Ethics. Keywords: Press Council, Journalists, Hoax News